Methylomes of renal cell lines and tumors or metastases differ significantly with impact on pharmacogenes - Winter, Stefan; Fisel, Pascale; Buettner, Florian; Rausch, Steffen; D'Amico, Debora; Hennenlotter, Joerg; Kruck, Stephan; Nies, Anne T.; Stenzl, Arnulf; Junker, Kerstin; Scharpf, Marcus; Hofmann, Ute; et al. (Scientific Reports, 2016)
Current therapies for metastatic clear cell renal cell carcinoma (ccRCC) show limited efficacy. Drug efficacy, typically investigated in preclinical cell line models during drug development, is influenced by pharmacogenes involved in targeting and disposition of drugs. Here we show through genome-wide DNA methylation profiling, that methylation patterns are concordant between primary ccRCC and macro-metastases irrespective of metastatic sites (rs >= 0.92). However, 195,038 (41%) of all investigated CpG sites, including sites within pharmacogenes, were differentially methylated (adjusted P < 0.05) in five established RCC cell lines compared to primary tumors, resulting in altered transcriptional expression. Exemplarily, gene-specific analyses of DNA methylation, mRNA and protein expression demonstrate lack of expression of the clinically important drug transporter OCT2 (encoded by SLC22A2) in cell lines due to hypermethylation compared to tumors or metastases. Our findings provide evidence that RCC cell lines are of limited benefit for prediction of drug effects due to epigenetic alterations. Similar epigenetic landscape of ccRCC-metastases and tumors opens new avenue for future therapeutic strategies.
EVALuna2:6920